1989
DOI: 10.3109/07853898909149205
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Myocardial Functions in Acute Hepatic Porphyrias. Role of Heme Arginate Administration

Abstract: In three patients with attacks of acute intermittent porphyria we found markedly impaired functions of the left ventricle accompanied by ECG changes that returned to normal after administration of heme arginate or cytochrome C administration. In nine patients with other types of porphyria, and in one patient with acute intermittent porphyria not suffering an attack, no significant changes of left ventricle function were observed. The changes seen in patients with an acute attack may be ascribed to acute myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…CoCl 2 , a short-term inducer of HO-1 expression and HO activity, has been reported to have exhib-98 ited antihypertensive effects in the same animal model described above for SnCl 2 (Sacerdoti et al, 1989). Metalloporphyrins, such as heme, heme arginate, and CoPP, are also commonly used to induce HO-1 expression and activity and have been used to normalize blood pressure in animals and humans (Kordac et al, 1989;Martasek et al, 1991). The side effects associated with their use are discussed elsewhere is this review.…”
Section: G Cardiovascular Drugs and Drug Developments Targeting Hemementioning
confidence: 99%
See 1 more Smart Citation
“…CoCl 2 , a short-term inducer of HO-1 expression and HO activity, has been reported to have exhib-98 ited antihypertensive effects in the same animal model described above for SnCl 2 (Sacerdoti et al, 1989). Metalloporphyrins, such as heme, heme arginate, and CoPP, are also commonly used to induce HO-1 expression and activity and have been used to normalize blood pressure in animals and humans (Kordac et al, 1989;Martasek et al, 1991). The side effects associated with their use are discussed elsewhere is this review.…”
Section: G Cardiovascular Drugs and Drug Developments Targeting Hemementioning
confidence: 99%
“…Subsequently, others reported that acute and chronic expression of HO-1 decreased vasoconstrictors, such as 20-HETE (Laniado- da Silva et al, 1994), thromboxane synthase activity (Sessa et al, 1989), and COX-2 activity (Abraham, 2003). Heme arginate, or heme, which is used clinically for the treatment of porphyria (Kordac et al, 1989), has been shown to have a beneficial effect on acute induction of HO-1 and lowers blood pressure in hypertensive rats (Schwartz-84 man et Martasek et al, 1991;Wang et al, 2006b). Hemin, a critical component of hemoglobin, is an active ingredient of a biological therapeutic agent approved by the U.S. Food and Drug Administration for the treatment of acute porphyrias.…”
Section: A Increased Levels Of Heme Oxygenase-1 and Heme Oxygenase Amentioning
confidence: 99%
“…Hence, the feasibility of heme as a therapy for broad medical indications appears to be questionable and needs further evaluation in clinical practice. A compound with better potential for translation into the clinic might be heme arginate, which appears to be less toxic than heme (Jeney et al, 2002) and is an approved therapy for treatment of hepatic porphyrias in various European countries (Mustajoki et al, 1986; Kordac et al, 1989). Notably, heme arginate was found to up-regulate HO-1 not only in healthy individuals (Doberer et al, 2010), but also in patients receiving deceased donor renal transplants in a recent phase IIB trial (Thomas et al, 2016).…”
Section: Protection Against Heme Toxicity Via Hemopexin and The Heme mentioning
confidence: 99%
“…Stannous chloride (SnCl 2 ) has been reported to lower blood pressure in spontaneously hypertensive rats (Sacerdoti et al, 1989). Metalloporphyrins, such as heme, heme arginate, and CoPP, are also commonly used drugs to induce HO-1 expression and HO activity and have been used to normalize blood pressure in animals and humans (Kordac et al, 1989; Levere et al, 1990; Abraham and Kappas, 2008). However, in discovering the ideal pharmacological drug, one must consider the dose and time of HO-1 induction.…”
Section: Introductionmentioning
confidence: 99%